Pan-cancer analysis of ADAMs: A promising biomarker for prognosis and response to chemotherapy and immunotherapy - Ma, Bo; Yu, Riyue (Frontiers in Genetics, 2023)
Background: Members of a disintegrin and metalloproteinase (ADAM) family play a vital role in cancer development. However, a comprehensive analysis of the landscape of the ADAM family in pan-cancer remains to be performed. Methods: The correlation of the expression level and prognostic value with ADAMs in a pan-cancer cohort and the relationship between ADAMs and the stemness score, tumour microenvironment (TME), chemotherapy-related drug sensitivity, immune subtype, and immunotherapy outcome were investigated. Results: ADAMs were differentially expressed between tumour and para-carcinoma tissues in the pan-cancer cohort, and the expression of ADAMs was significantly correlated with patient prognosis. Furthermore, ADAMs were significantly correlated with the stromal score and immune score based on the TME analysis. Additionally, ADAMs were also correlated with DNAss and RNAss in the pan-cancer cohort. On investigating the CellMiner database, ADAMs were revealed to be significantly correlated with the sensitivity of various drugs, including raloxifene and tamoxifen. Moreover, in the IMvigor210 and GSE78220 cohorts, ADAMs were correlated with immunotherapy response and immune activation genes. Furthermore, quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) were utilised to determine the differential level of ADAM9 in cancer and para-carcinoma tissues in patients’ samples. Conclusion: This study elucidates the importance of ADAMs in cancer progression and lays a foundation for further exploration of ADAMs as potential pan-cancer targets.